2019
DOI: 10.1186/s41155-019-0126-3
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of a dissonance-based eating disorders prevention program with Brazilian girls

Abstract: Background: Given that most young women with eating disorders do not receive treatment, implementing effective prevention programs is a public health priority. The Body Project is a group-based eating disorder prevention program with evidence of both efficacy and effectiveness. This trial evaluated the efficacy of this prevention program with Brazilian girls, as no published study has tested whether this intervention is culturally sensitive and efficacious with Latin-American adolescents. Methods: Female stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 54 publications
1
18
0
11
Order By: Relevance
“…This evidence is consistent with Bronfenbrenner's ecological systems theory [30,31], which proposes that interactions with parents around learned topics at school might help address internalizing concerns [4,32]. Digital-based prevention programs were suggested for this purpose [33][34][35].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This evidence is consistent with Bronfenbrenner's ecological systems theory [30,31], which proposes that interactions with parents around learned topics at school might help address internalizing concerns [4,32]. Digital-based prevention programs were suggested for this purpose [33][34][35].…”
Section: Discussionsupporting
confidence: 77%
“…Participants' attrition presents a significant problem for even the most well-planned and well-executed intervention projects with internal and external validity and facilitator motivation. For instance, Amaral et al reported that 50% of intervention participants attended all four prevention program sessions and completed the posttest assessment [34]. Morgan et al reported that only 38% of the parents that participated in mental health first aid training completed the 3-yrs follow-up assessment [35] However, the retention rate was higher when the concurrent parental component was delivered by WhatsApp than by a specially designed application.…”
Section: Discussionmentioning
confidence: 99%
“…No campo de prevenção dos transtornos alimentares, algumas estratégias já foram desenvolvidas, com destaque para programas de prevenção direcionados para populações seletivas, ou seja, aquelas como maiores riscos de desenvolvimento de transtornos alimentares 37 , como é o caso de estudantes de Nutrição. Programas preventivos com base na dissonância cognitiva têm demonstrado elevada eficácia e eficiência em populações seletivas 11,37 e podem ser implementados no contexto de formação de estudantes de Nutrição como uma estratégia de prevenção de desenvolvimento de transtornos alimentares.…”
Section: Discussionunclassified
“…O modelo teórico biopsicossocial 10 propõe que o uso da mídia social é determinante na internalização de ideais de corpo propagados socialmente, que, por sua vez, pode gerar dois desfechos: a insatisfação corporal e a restrição alimentar. Cabe destacar que esses últimos são considerados fatores de risco para o desenvolvimento de transtornos alimentares, sendo considerados ainda preditores dos comportamentos alimentares disfuncionais 11 . Portanto, entender a internalização desses ideais é fundamental.…”
Section: Introductionunclassified
“…Diversos autores apontam dificuldades na implementação das intervenções, como o acesso às escolas, a adesão das alunas aos programas, a falta de estrutura física, de materiais e de recursos financeiros, o que impossibilita o desenvolvimento de programas de maior abrangência em solo brasileiro . Propostas presenciais que se utilizam da dissonância cognitiva têm sido desenvolvida no país, mas ainda são restritas a pequenos grupos (Amaral et al,2019;Almeida et al,2021). O programa "StayingFit Brasil" é a única proposta online que poderia ser replicada e pensada como uma abordagem virtual de maior abrangência no país, sendo necessário ser testado quanto a seus efeitos na redução de sintomas de TA (Silva et al, 2019).…”
Section: Perspectivas Futuras Em Países Em Desenvolvimentounclassified